Toughened aluminum oxide ceramic and preparation method thereof

By introducing toughening agents such as nanocellulose and graphene into alumina ceramics, combined with hydrothermal reaction and ball milling technology, the problem of low fracture toughness of alumina ceramic materials is solved, and the mechanical properties and high temperature stability of the ceramics are significantly improved. The performance improvement of ceramic materials has been achieved.

CN119191823AActive Publication Date: 2024-12-27XINHUA COUNTY SHUNDA ELECTRONIC CERAMICS CO LTD

Patent Information

Application Number
CN202411457889.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-18
Publication Date
2024-12-27
Estimated Expiration
2044-10-18

AI Technical Summary

Technical Problem

The existing alumina ceramic materials have low fracture toughness and are difficult to meet the needs of ceramic materials in terms of mechanical properties and wear resistance.

Method used

Toughening alumina ceramics are prepared by combining nanocellulose and graphene with high-purity alumina powder through hydrothermal reaction and ball milling. Nanocellulose is used as toughening phase to significantly improve the fracture toughness of the ceramics and Relative strength and stable crystal phase is generated through high-temperature sintering, hindering the high-temperature phase change reaction.

Benefits of technology

It significantly improves the fracture toughness and high temperature stability of ceramic materials, enhances its mechanical properties and wear resistance, and improves the overall performance of ceramics.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention discloses toughened aluminum oxide ceramic and a preparation method of the toughened aluminum oxide ceramic. The invention relates to the technical field of alumina ceramics, and relates to the technical field of alumina ceramics. The alumina ceramics comprise, by weight, 2-6 parts of clay, 20-30 parts of nano aluminum powder, 70-90 parts of alumina powder, 8-12 parts of concentrated sulfuric acid, 8-12 parts of microcrystalline cellulose, 3-4 parts of a sintering aid, 3-4 parts of quartz, 3-4 parts of calcite, 12-16 parts of graphene and 5-7 parts of a binder. A compression molding method is adopted, nanofibers are evenly added into a ceramic material, the nanofibers serve as a toughening phase of a matrix, the fracture toughness and the relative strength of the composite material are remarkably enhanced, and when fiber-reinforced ceramic is fractured, through pulling-out, bridging, debonding and fracture of the fibers, the strength of the composite material is greatly improved. And the surface energy increment during fracture is improved in manners of micronization, bending, deflection and the like of cracks, so that the toughness is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of alumina ceramics, in particular to a toughened alumina ceramic and a preparation method thereof. Background Art

[0002] Alumina ceramic materials have excellent mechanical and electrical properties and low manufacturing costs. They are currently the most widely used advanced ceramic materials. High-purity submicron alumina ultrafine powders have been used to prepare alumina precision ceramic materials with a bending strength of up to 700-1000Mpa. However, the fracture toughness of this material is very low, usually only 3-4Mpa·m1 / 2. Therefore, improving the fracture toughness of alumina ceramics has always been the goal that ceramic material workers have been looking forward to and working hard on.

[0003] There are generally four methods for ceramic toughening: dispersion toughening, phase change toughening, fiber and whisker toughening, and the recently developed carbon nanotube toughening. Among them, the effect of dispersion toughening is very limited; although the phase change toughening of zirconia ceramics can increase the fracture toughness of the material by 2 to 3 times, the effect of phase change toughening drops sharply with the increase of temperature; carbon nanotubes are easily damaged in the process of mass production, dispersion and subsequent sintering, and the synthesis process is complex and expensive, so their application is limited. The obvious toughening effect and good high temperature performance make the use of fiber and whisker toughening the first choice and research focus of ceramic toughening.

[0004] Due to their excellent mechanical properties and the toughening effects such as crack deflection, crack bridging and whisker pullout, the room temperature and high temperature flexural strength and fracture toughness, thermal shock resistance, wear resistance and creep properties of ceramic composites toughened by fibers or whiskers have been improved to varying degrees.

[0005] There are many methods for forming alumina ceramic products, including dry pressing, grouting, extrusion, cold isostatic pressing, injection, casting, hot pressing and hot isostatic pressing. In recent years, domestic and foreign countries have developed forming technologies such as filter press molding, direct solidification injection molding, gel injection molding, centrifugal grouting molding and solid free molding. Different product shapes, sizes, complex shapes and precision products require different forming methods.

[0006] Dry pressing: Alumina ceramic dry pressing technology is limited to objects with simple shapes, inner wall thickness exceeding 1mm, and length-to-diameter ratio not greater than 4:1. The forming methods are uniaxial or bidirectional. There are two types of presses: hydraulic and mechanical, which can be semi-automatic or fully automatic. The maximum pressure of the press is 200Mpa. The output can reach 15 to 50 pieces per minute. Since the stroke pressure of the hydraulic press is uniform, the height of the pressed parts is different when there is a difference in powder filling. Slurry injection molding: Slurry injection molding is the earliest molding method used for alumina ceramics. Because of the use of gypsum molds, low cost and easy molding of large-sized and complex-shaped parts. The key to slurry injection molding is the preparation of alumina slurry. Usually water is used as the flux medium, and then the debonding agent and binder are added. After sufficient grinding, the exhaust is exhausted and then poured into the gypsum mold.

[0007] Existing ceramic composite materials are deficient in fracture toughness and relative strength, the mechanical properties of ceramics are relatively poor, and cracks and fractures are easily present on the ceramic surface, which affects the quality of the ceramics. Summary of the invention

[0008] In order to solve the above technical problems, the present invention provides a toughened alumina ceramic, comprising the following components in parts by weight: 2-6 parts by weight of clay, 15-35 parts by weight of nano-aluminum powder, 65-95 parts by weight of alumina powder, 6-14 parts by weight of concentrated sulfuric acid, 6-14 parts by weight of microcrystalline cellulose, 2-5 parts by weight of sintering aid, 2-5 parts by weight of quartz, 2-5 parts by weight of calcite, 12-16 parts by weight of graphene and 5-7 parts by weight of binder; The method for preparing the aluminum oxide powder comprises the following steps: Step A1: selecting aluminum salt as an aluminum source and performing recrystallization treatment on the aluminum salt to improve the purity; Step A2: weigh the purified aluminum salt and calculate the amount of the required precipitant (ammonia water) according to the chemical reaction stoichiometric ratio; Step A3: Deionized water is used as the solvent, and the conductivity of the water is controlled to be below 1 μS / cm; Step A4: Select sodium dodecylbenzene sulfonate, accurately weigh the amount, and prepare a solution with a concentration of 0.01-0.05 mol / L with deionized water for later use; Step A5: under stirring conditions, slowly drop the aluminum salt solution into the precipitant solution, monitor the pH, and after the dropwise addition is completed, continue to stir the reaction for 1-2 hours to allow the reaction to proceed fully to obtain aluminum hydroxide precipitate; Then, an aging treatment is performed, and the reaction system is allowed to stand for aging for 6-12 hours, and the aging temperature is controlled at 30-40° C. to obtain an aluminum hydroxide precursor; Step A6: washing the aluminum hydroxide precursor by multiple centrifugal washings, and after washing, using a vacuum filtration device for solid-liquid separation, using a microporous filter membrane with a pore size of 0.1-0.2 μm to obtain a pure aluminum hydroxide precursor; Step A7: The washed aluminum hydroxide precursor is transferred to a high-pressure reactor, deionized water is added according to a solid-liquid ratio of 1:10-1:20 g / mL, and the previously prepared organic additive solution is added, the reactor is sealed, and then placed in a heating furnace for hydrothermal reaction; Step A8: After the hydrothermal reaction is completed, the reactor is allowed to cool naturally to room temperature. After cooling, centrifugal separation is performed again to separate the plate-like crystalline alumina powder. The separated plate-like alumina powder is dried in a vacuum drying oven. The dried product is ground using an agate mortar to obtain the final plate-like crystalline alumina powder.

[0009] A method for preparing toughened alumina ceramics comprises the following steps: Step 1: Preparation of toughening material: prepare a reaction kettle, inject concentrated sulfuric acid and microcrystalline cellulose into the reactor to mix, and complete the preparation of nanocellulose; Step 2: Preparation of ceramic powder: Nano-aluminum powder and high-purity alumina powder are used as initial raw materials, mixed evenly, and the mixed slurry is dried and ground to obtain ceramic powder; Step 3: Mix the ceramic powder and the sintering aid, use distilled water as a ball milling medium, and perform ball milling on the mixed materials to obtain an alumina slurry; Step 4: adding nanocellulose to alumina slurry for ball milling, and obtaining a mixed slurry after uniform dispersion; Step 5: mixing the mixed slurry with clay, quartz, graphene, calcite and a binder to obtain a mixed blank; Step six: granulate, press-form, dry and sinter the mixed blank to obtain toughened alumina ceramics.

[0010] The aluminum oxide is aluminum oxide powder with a purity of ≥99.9%; The average particle size D50 of the aluminum oxide is 0.3 to 0.4 μm; The magnesium oxide is magnesium oxide powder of no less than analytical purity; The average particle size D50 of the magnesium oxide is 0.2 to 0.4 μm; The zirconium oxide is a zirconium oxide powder of no less than analytical purity; The average particle size D50 of the zirconium oxide is 0.1-0.3 μm.

[0011] Preferably, the method for preparing nanocellulose comprises the following steps: Step 1: prepare a measuring cup, put 10 parts by weight of microcrystalline cellulose into the reactor, then take out 300-400 ml of 45-65% concentrated sulfuric acid and put it into the reactor, and use an external heating device to heat the entire reactor; Step 2: The heating time is controlled within 30-50 minutes. After the color changes after heating, add an appropriate amount of water directly into the reactor, and use an external centrifugal device for stirring and precipitation; Step 3: Screen the precipitates produced after stirring in batches, with 60 ml as one measurement, and screen the precipitates of the same proportion to extract nanocellulose.

[0012] Preferably, the sintering aid includes at least one of calcium oxide, magnesium oxide, silicon dioxide, lanthanum oxide and titanium dioxide.

[0013] Preferably, the sintering aid is a mixture of titanium dioxide and magnesium oxide, and the mass ratio of titanium dioxide to magnesium oxide in the mixture is 1 to 3:1.

[0014] Preferably, the sintering aid is prepared according to the following method: titanium dioxide and magnesium oxide are mixed in a mass ratio, zirconium oxide is used as a ball milling ball, the speed of the ball mill is controlled to be 700-900r / min, the ball milling time is controlled to be 4-8h, and dry ball milling is performed to obtain it.

[0015] Preferably, the pressing process in step six is ​​performed by an external pressing device, and the pressing time and pressing weight are effectively controlled, the pressing time is controlled at 2-5 minutes, and the pressing weight is set at 5-10N.

[0016] The pressing preferably includes one of roll forming, isostatic pressing and axial pressing; the pressing pressure is preferably 100-500 MPa, more preferably 200-300 MPa; the pressing time is preferably 1-5 min, more preferably 2-3 min.

[0017] Preferably, the drying in step six refers to drying the pressed green body, cutting and segmenting the dried green body, and drying multiple groups of green bodies after different segments in batches. When the green body is dried, the drying temperature is set at 50-80°C and the drying time is set at 8-12h.

[0018] The above-mentioned formed green body is dried in stages to obtain a nanofiber-modified ceramic green body, specifically: the green body is dried in stages, dried at 40-60°C for 10-12 hours; kept warm at 60-80°C for 10-12 hours; and kept warm at 80-100°C for 22-24 hours.

[0019] Preferably, the sintering in step six refers to placing the green body after segmented drying in a sintering furnace, controlling the sintering temperature at 1400-1600° C., and controlling the sintering time at 5-7 min to prepare a toughened alumina ceramic green body.

[0020] The sintering temperature is preferably 1200-1500°C, more preferably 1300-1400°C; the sintering time is preferably 30-120 min, more preferably 60-100 min, more preferably 80-90 min. In the present invention, the sintering can increase the density of the pressed green body, thereby improving the mechanical properties of the composite material.

[0021] The sintering is preferably performed by vacuum sintering; the vacuum degree of the vacuum sintering is preferably not higher than 3×-110 Pa.

[0022] The present invention provides a toughened alumina ceramic and a preparation method thereof, which has the following beneficial effects: 1. The present invention adopts the method of adding nanofibers to improve the mechanical properties of ceramics. The nanofibers are uniformly added to the ceramic material by a pressing molding method. The nanofibers serve as a toughening phase of the matrix, which significantly enhances the fracture toughness and relative strength of the composite material. 2. The nanofibers used in the present invention have a smaller fiber diameter, and their specific surface area is generally 1-2 orders of magnitude larger than that of micron-grade fibers. For fiber-reinforced ceramics, the process of ceramic material fracture is essentially a process of increasing surface energy. When fiber-reinforced ceramics fracture, the surface energy increment at the time of fracture is increased by fiber pulling out, bridging, debonding and fracture, as well as crack miniaturization, bending and deflection, thereby improving toughness; 3. The presence of nanofibers as a reinforcement phase during the high-temperature sintering process of the present invention provides a large interface area and size effect, can generate a stable crystalline phase, effectively hinder the occurrence of phase change reactions at high temperatures, improve the stability of fiber-reinforced ceramics, and improve their toughness and strength after high-temperature sintering; 4. The alumina ceramic composite material provided by the present invention uses alumina as a matrix, and by adjusting the content, graphene and zirconium oxide have a synergistic toughening effect, thereby improving the toughness of the alumina ceramic material. DETAILED DESCRIPTION

[0023] The following specific embodiments further describe the present invention in detail. The embodiments of the present invention are provided for the purpose of illustration and description, and are not intended to be exhaustive or to limit the present invention to the disclosed forms. Many modifications and variations will be apparent to those of ordinary skill in the art. The embodiments are selected and described to better illustrate the principles and practical applications of the present invention, and to enable those of ordinary skill in the art to understand the present invention and thereby design various embodiments with various modifications suitable for specific uses.

[0024] Embodiment 1: A toughened alumina ceramic, comprising the following components in parts by weight: 4 parts by weight of clay, 25 parts by weight of nano-aluminum powder, 80 parts by weight of alumina powder, 10 parts by weight of concentrated sulfuric acid, 10 parts by weight of microcrystalline cellulose, 3.5 parts by weight of a sintering aid, 3.5 parts by weight of quartz, 3.5 parts by weight of calcite, 14 parts by weight of graphene, and 6 parts by weight of a binder; The method for preparing the aluminum oxide powder comprises the following steps: 1. Aluminum source selection and purification Choose high-purity aluminum salt as the aluminum source, such as analytical grade aluminum nitrate or aluminum sulfate. Recrystallize and purify the aluminum salt to further improve its purity. Take aluminum nitrate as an example, dissolve it in an appropriate amount of deionized water, heat it until it is completely dissolved, slowly cool it to crystallize, collect the crystallized product by filtration, and repeat this operation 2-3 times to remove impurity ions; Accurately weigh the purified aluminum salt, accurately calculate the amount of precipitant (such as ammonia water) required according to the chemical reaction stoichiometric ratio, and prepare a slightly excess amount of precipitant in consideration of the fine-tuning of the pH value in the subsequent reaction system.

[0025] 2. Preparation of solvents and additives Deionized water was used as the solvent and the conductivity of the water was controlled below 1 μS / cm to reduce the effect of impurities in the water on the reaction; Prepare organic additives, such as polyethylene glycol (PEG) or sodium dodecylbenzene sulfonate (SDBS). For polyethylene glycol, choose a molecular weight range of 2000-6000, accurately weigh a certain amount according to the experimental requirements, and dissolve it in a small amount of deionized water to prepare a solution for use; for sodium dodecylbenzene sulfonate, accurately weigh an appropriate amount and use deionized water to prepare a solution with a concentration of 0.01-0.05 mol / L.

[0026] 3. Precursor preparation stage 4. Precipitation reaction operation Under stirring conditions, slowly drop the aluminum salt solution into the precipitant solution, and use a precision pH meter to monitor the pH value of the reaction system in real time. By coordinating the dropping speed and the stirring speed, the pH value of the reaction system is maintained within a stable range (e.g., for ammonia precipitant, the pH value is stabilized at 9-10). The stirring speed is first set at 200-300rpm, and can be appropriately reduced to 100-150rpm in the later stage of the dropping to avoid excessive bubbles; After the addition is completed, the reaction is continued to be stirred for 1-2 hours to allow the reaction to proceed fully and obtain aluminum hydroxide precipitation. Then, an aging treatment is performed, and the reaction system is allowed to stand for 6-12 hours, and the aging temperature is controlled at 30-40°C, which is conducive to the growth and stability of the precipitated particles.

[0027] 5. Precursor washing and separation The aluminum hydroxide precursor is washed by multiple centrifugal washing. The centrifugal speed is set at 3000-5000rpm each time, and the centrifugal time is 10-15 minutes. The amount of deionized water used for washing is 3-5 times the mass of the precursor, and the number of washings is 3-5 times to ensure that the impurity ions remaining in the precursor are removed; After washing, a vacuum filtration device is used for solid-liquid separation, and a microporous filter membrane with a pore size of 0.1-0.2 μm is selected to ensure a good filtration effect and obtain a pure aluminum hydroxide precursor filter cake.

[0028] 6. Reactor pretreatment Clean and dry the autoclave. Rinse the inner wall of the autoclave with deionized water for 3-5 times, and then dry it in an oven at 80-100°C for 2-3 hours. Apply a thin layer of polytetrafluoroethylene coating evenly on the inner wall of the autoclave to prevent the product from sticking to the autoclave wall during the reaction.

[0029] Hydrothermal reaction parameter control Transfer the washed aluminum hydroxide precursor to a high-pressure reactor, add deionized water at a solid-liquid ratio (ratio of precursor mass to water volume) of 1:10-1:20 (g / mL), and add the previously prepared organic additive solution. After sealing the reactor, place it in a heating furnace for hydrothermal reaction. The reaction temperature is set at 150-180°C, and the reaction pressure is automatically adjusted according to the relationship between the saturated vapor pressure of water and the reaction temperature. The reaction time is 12-24 hours. During the heating process, the heating rate is controlled at 2-3°C / min to avoid the influence of too rapid temperature changes on the product crystal form.

[0030] 7. Cooling and separation After the hydrothermal reaction is completed, the reactor is allowed to cool naturally to room temperature. During the cooling process, the pressure inside the reactor is gradually reduced to avoid rapid pressure reduction leading to product structure destruction. After cooling, centrifugal separation is performed again, and the centrifugal parameters are the same as those during the precursor washing. The solid product obtained by separation is the initially prepared plate-like crystalline alumina powder.

[0031] 8. Drying and grinding The separated plate-like alumina powder is dried in a vacuum drying oven. The drying temperature is set at 60-80°C, the vacuum degree is controlled at -0.08-0.1MPa, and the drying time is 8-12 hours. The dried product is ground using an agate mortar to avoid introducing impurities during the grinding process to obtain the final plate-like crystalline alumina powder product. The particle size distribution and micromorphology of the product are detected and analyzed by a laser particle size analyzer and a scanning electron microscope to evaluate the product quality.

[0032] A method for preparing toughened alumina ceramics comprises the following steps: Step 1: Preparation of toughening material: prepare a reaction kettle, inject concentrated sulfuric acid and microcrystalline cellulose into the reactor to mix, and complete the preparation of nanocellulose; Step 2: Preparation of ceramic powder: Nano-aluminum powder and high-purity alumina powder are used as initial raw materials, mixed evenly, and the mixed slurry is dried and ground to obtain ceramic powder; Step 3: Mix the ceramic powder and the sintering aid, use distilled water as a ball milling medium, and perform ball milling on the mixed materials to obtain an alumina slurry; Step 4: adding nanocellulose to alumina slurry for ball milling, and obtaining a mixed slurry after uniform dispersion; Step 5: mixing the mixed slurry with clay, quartz, graphene, calcite and a binder to obtain a mixed blank; Step six: granulate, press-form, dry and sinter the mixed blank to obtain toughened alumina ceramics.

[0033] The grinding process of the present invention is preferably carried out in a ball mill, and the speed of the ball mill is preferably 400-500 r / min; the time of the ball mill is preferably 1-1.5 h, and more preferably 1.2-1.3 h. The present invention has no particular limitation on the model of the ball mill, and a ball mill well known to those skilled in the art can be used. The present invention can achieve uniform dispersion of the raw materials by controlling the speed and time of the ball mill.

[0034] The sintering aid includes at least one of calcium oxide, magnesium oxide, silicon dioxide, lanthanum oxide and titanium dioxide.

[0035] The sintering aid is a mixture of titanium dioxide and magnesium oxide, and the mass ratio of titanium dioxide to magnesium oxide in the mixture is 1 to 3:1.

[0036] The sintering aid is prepared according to the following method: titanium dioxide and magnesium oxide are mixed according to a mass ratio, zirconium oxide is used as a ball milling ball, the speed of the ball mill is controlled to be 700-900r / min, the ball milling time is controlled to be 4-8h, and dry ball milling is performed to obtain it.

[0037] The pressing process in step six is ​​performed by using an external pressing device, and the pressing time and pressing weight are effectively controlled. The pressing time is controlled at 2-5 minutes, and the pressing weight is set at 5-10N.

[0038] The drying in step six refers to drying the pressed green body, cutting and segmenting the dried green body, and batch drying multiple groups of green bodies after different segments. When the green body is drying, the drying temperature is set at 50-80°C and the drying time is set at 8-12h.

[0039] The sintering in step six refers to placing the green body after segmented drying in a sintering furnace, controlling the sintering temperature at 1400-1600° C., and controlling the sintering time at 5-7 minutes to prepare a toughened alumina ceramic green body.

[0040] Embodiment 2: A toughened alumina ceramic, comprising the following components in weight: 4 parts by weight of clay, 25 parts by weight of nano-aluminum powder, 80 parts by weight of alumina powder, 10 parts by weight of concentrated sulfuric acid, 10 parts by weight of microcrystalline cellulose, 3.5 parts by weight of a sintering aid, 3.5 parts by weight of quartz, 3.5 parts by weight of calcite, 14 parts by weight of graphene, and 6 parts by weight of a binder; A method for preparing toughened alumina ceramics comprises the following steps: Step 1: Preparation of toughening material: prepare a reaction kettle, inject concentrated sulfuric acid and microcrystalline cellulose into the reactor to mix, and complete the preparation of nanocellulose; Step 2: Preparation of ceramic powder: Nano-aluminum powder and high-purity alumina powder are used as initial raw materials, mixed evenly, and the mixed slurry is dried and ground to obtain ceramic powder; Step 3: Mix the ceramic powder and the sintering aid, use distilled water as a ball milling medium, and perform ball milling on the mixed materials to obtain an alumina slurry; Step 4: adding nanocellulose to alumina slurry for ball milling, and obtaining a mixed slurry after uniform dispersion; Step 5: mixing the mixed slurry with clay, quartz, graphene, calcite and a binder to obtain a mixed blank; Step six: granulate, press-form, dry and sinter the mixed blank to obtain toughened alumina ceramics.

[0041] The grinding process of the present invention is preferably carried out in a ball mill, and the speed of the ball mill is preferably 400-500 r / min; the time of the ball mill is preferably 1-1.5 h, and more preferably 1.2-1.3 h. The present invention has no particular limitation on the model of the ball mill, and a ball mill well known to those skilled in the art can be used. The present invention can achieve uniform dispersion of the raw materials by controlling the speed and time of the ball mill.

[0042] The method for preparing nanocellulose in step 3 comprises the following steps: Step 1: prepare a measuring cup, put 10 parts by weight of microcrystalline cellulose into the reactor, then take out 300-400 ml of 45-65% concentrated sulfuric acid and put it into the reactor, and use an external heating device to heat the entire reactor; Further, concentrated sulfuric acid was slowly added dropwise to the reaction kettle, and stirring was maintained during the addition process, and the stirring speed was controlled at 100-150 r / min; Step 2: The heating time is controlled within 30-50 minutes. After the color changes after heating, add an appropriate amount of water directly into the reactor, and use an external centrifugal device for stirring and precipitation; It is further explained that the reactor is heated by an intelligent temperature control system, and the heating temperature is set to 55-60°C. When the reaction material changes color after heating, the heating is stopped, and an appropriate amount of water is added through the automatic feeding system of the reactor (the ratio of water added is 5 times the volume of concentrated sulfuric acid), and then the high-speed stirring device is started, and the stirring speed is increased to 500-600r / min, and the stirring time is continued for 10-15min, so that the reaction product is fully dispersed in the water; After the stirring is completed, the centrifugal sedimentation mode is immediately switched to, the centrifugal speed is controlled at 400-450r / min, and the centrifugal time is set to 15-20min; Step 3: Screen the precipitates produced after stirring in batches, with 60 ml as one measurement, and screen the precipitates of the same proportion to extract nanocellulose; It is further explained that after the centrifugation, the precipitated material is transferred to an automatic screening device, which sets multiple layers of sieves with different apertures according to the particle size distribution characteristics of nanocellulose, arranged in order from large to small, with the aperture of the top sieve being 0.5 μm, and decreasing in sequence to the aperture of the bottom sieve being 0.05 μm; During the screening process, the precipitate intercepted by each layer of the sieve is collected and measured separately, with 60 ml as a measuring unit. The nanocellulose that meets the particle size requirements is combined and collected as a toughening material in the subsequent preparation process. The centrifugal speed inside the external centrifugal device is controlled at 350 r / min, the heating temperature is controlled at 50° C., and the proportion of water added is 5 times that of concentrated sulfuric acid liquid.

[0043] The sintering aid includes at least one of calcium oxide, magnesium oxide, silicon dioxide, lanthanum oxide and titanium dioxide.

[0044] The sintering aid is a mixture of titanium dioxide and magnesium oxide, and the mass ratio of titanium dioxide to magnesium oxide in the mixture is 1 to 3:1.

[0045] The sintering aid is prepared according to the following method: titanium dioxide and magnesium oxide are mixed according to a mass ratio, zirconium oxide is used as a ball milling ball, the speed of the ball mill is controlled to be 700-900r / min, the ball milling time is controlled to be 4-8h, and dry ball milling is performed to obtain it.

[0046] The pressing process in step six is ​​performed by using an external pressing device, and the pressing time and pressing weight are effectively controlled. The pressing time is controlled at 2-5 minutes, and the pressing weight is set at 5-10N.

[0047] The drying in step six refers to drying the pressed green body, cutting and segmenting the dried green body, and batch drying multiple groups of green bodies after different segments. When the green body is drying, the drying temperature is set at 50-80°C and the drying time is set at 8-12h.

[0048] The sintering in step six refers to placing the green body after segmented drying in a sintering furnace, controlling the sintering temperature at 1400-1600° C., and controlling the sintering time at 5-7 minutes to prepare a toughened alumina ceramic green body.

[0049] Embodiment 3, a toughened alumina ceramic, comprising the following components in weight: 4 parts by weight of clay, 25 parts by weight of nano-aluminum powder, 80 parts by weight of alumina powder, 10 parts by weight of concentrated sulfuric acid, 10 parts by weight of microcrystalline cellulose, 3.5 parts by weight of a sintering aid, 3.5 parts by weight of quartz, 3.5 parts by weight of calcite, 14 parts by weight of graphene, and 6 parts by weight of a binder; The method for preparing the aluminum oxide powder comprises the following steps: 1. Aluminum source selection and purification Choose high-purity aluminum salt as the aluminum source, such as analytical grade aluminum nitrate or aluminum sulfate. Recrystallize and purify the aluminum salt to further improve its purity. Take aluminum nitrate as an example, dissolve it in an appropriate amount of deionized water, heat it until it is completely dissolved, slowly cool it to crystallize, collect the crystallized product by filtration, and repeat this operation 2-3 times to remove impurity ions; Accurately weigh the purified aluminum salt, accurately calculate the amount of precipitant (such as ammonia water) required according to the chemical reaction stoichiometric ratio, and prepare a slightly excess amount of precipitant in consideration of the fine-tuning of the pH value in the subsequent reaction system.

[0050] 2. Preparation of solvents and additives Deionized water was used as the solvent and the conductivity of the water was controlled below 1 μS / cm to reduce the effect of impurities in the water on the reaction; Prepare organic additives, such as polyethylene glycol (PEG) or sodium dodecylbenzene sulfonate (SDBS). For polyethylene glycol, choose a molecular weight range of 2000-6000, accurately weigh a certain amount according to the experimental requirements, and dissolve it in a small amount of deionized water to prepare a solution for use; for sodium dodecylbenzene sulfonate, accurately weigh an appropriate amount and use deionized water to prepare a solution with a concentration of 0.01-0.05 mol / L.

[0051] 3. Precursor preparation stage 4. Precipitation reaction operation Under stirring conditions, slowly drop the aluminum salt solution into the precipitant solution, and use a precision pH meter to monitor the pH value of the reaction system in real time. By coordinating the dropping speed and the stirring speed, the pH value of the reaction system is maintained within a stable range (e.g., for ammonia precipitant, the pH value is stabilized at 9-10). The stirring speed is first set at 200-300rpm, and can be appropriately reduced to 100-150rpm in the later stage of the dropping to avoid excessive bubbles; After the addition is completed, the reaction is continued to be stirred for 1-2 hours to allow the reaction to proceed fully and obtain aluminum hydroxide precipitation. Then, an aging treatment is performed, and the reaction system is allowed to stand for 6-12 hours, and the aging temperature is controlled at 30-40°C, which is conducive to the growth and stability of the precipitated particles.

[0052] 5. Precursor washing and separation The aluminum hydroxide precursor is washed by multiple centrifugal washing. The centrifugal speed is set at 3000-5000rpm each time, and the centrifugal time is 10-15 minutes. The amount of deionized water used for washing is 3-5 times the mass of the precursor, and the number of washings is 3-5 times to ensure that the impurity ions remaining in the precursor are removed; After washing, a vacuum filtration device is used for solid-liquid separation, and a microporous filter membrane with a pore size of 0.1-0.2 μm is selected to ensure a good filtration effect and obtain a pure aluminum hydroxide precursor filter cake.

[0053] 6. Reactor pretreatment Clean and dry the autoclave. Rinse the inner wall of the autoclave with deionized water for 3-5 times, and then dry it in an oven at 80-100°C for 2-3 hours. Apply a thin layer of polytetrafluoroethylene coating evenly on the inner wall of the autoclave to prevent the product from sticking to the autoclave wall during the reaction.

[0054] Hydrothermal reaction parameter control Transfer the washed aluminum hydroxide precursor to a high-pressure reactor, add deionized water at a solid-liquid ratio (ratio of precursor mass to water volume) of 1:10-1:20 (g / mL), and add the previously prepared organic additive solution. After sealing the reactor, place it in a heating furnace for hydrothermal reaction. The reaction temperature is set at 150-180°C, and the reaction pressure is automatically adjusted according to the relationship between the saturated vapor pressure of water and the reaction temperature. The reaction time is 12-24 hours. During the heating process, the heating rate is controlled at 2-3°C / min to avoid the influence of too rapid temperature changes on the product crystal form.

[0055] 7. Cooling and separation After the hydrothermal reaction is completed, the reactor is allowed to cool naturally to room temperature. During the cooling process, the pressure inside the reactor is gradually reduced to avoid rapid pressure reduction leading to product structure destruction. After cooling, centrifugal separation is performed again, and the centrifugal parameters are the same as those during the precursor washing. The solid product obtained by separation is the initially prepared plate-like crystalline alumina powder.

[0056] 8. Drying and grinding The separated plate-like alumina powder is dried in a vacuum drying oven. The drying temperature is set at 60-80°C, the vacuum degree is controlled at -0.08-0.1MPa, and the drying time is 8-12 hours. The dried product is ground using an agate mortar to avoid introducing impurities during the grinding process to obtain the final plate-like crystalline alumina powder product. The particle size distribution and micromorphology of the product are detected and analyzed by a laser particle size analyzer and a scanning electron microscope to evaluate the product quality.

[0057] A method for preparing toughened alumina ceramics comprises the following steps: Step 1: Preparation of toughening material: prepare a reactor, inject concentrated sulfuric acid and microcrystalline cellulose into the reactor to mix, and complete the preparation of nanocellulose; Step 2: Preparation of ceramic powder: Nano-aluminum powder and high-purity alumina powder are used as initial raw materials, mixed evenly, and the mixed slurry is dried and ground to obtain ceramic powder; Step 3: Mix the ceramic powder and the sintering aid, use distilled water as a ball milling medium, and perform ball milling on the mixed materials to obtain an alumina slurry; Step 4: adding nanocellulose to alumina slurry for ball milling, and obtaining a mixed slurry after uniform dispersion; Step 5: mixing the mixed slurry with clay, quartz, graphene, calcite and a binder to obtain a mixed blank; Step six: granulate, press-form, dry and sinter the mixed blank to obtain toughened alumina ceramics.

[0058] The grinding process of the present invention is preferably carried out in a ball mill, and the speed of the ball mill is preferably 400-500 r / min; the time of the ball mill is preferably 1-1.5 h, and more preferably 1.2-1.3 h. The present invention has no particular limitation on the model of the ball mill, and a ball mill well known to those skilled in the art can be used. The present invention can achieve uniform dispersion of the raw materials by controlling the speed and time of the ball mill.

[0059] The method for preparing nanocellulose in step 3 comprises the following steps: Step 1: prepare a measuring cup, put 10 parts by weight of microcrystalline cellulose into the reactor, then take out 300-400 ml of 45-65% concentrated sulfuric acid and put it into the reactor, and use an external heating device to heat the entire reactor; Further, concentrated sulfuric acid was slowly added dropwise to the reaction kettle, and stirring was maintained during the addition process, and the stirring speed was controlled at 100-150 r / min; Step 2: The heating time is controlled within 30-50 minutes. After the color changes after heating, add an appropriate amount of water directly into the reactor, and use an external centrifugal device for stirring and precipitation; It is further explained that the reactor is heated by an intelligent temperature control system, and the heating temperature is set to 55-60°C. When the reaction material changes color after heating, the heating is stopped, and an appropriate amount of water is added through the automatic feeding system of the reactor (the ratio of water added is 5 times the volume of concentrated sulfuric acid), and then the high-speed stirring device is started, and the stirring speed is increased to 500-600r / min, and the stirring time is continued for 10-15min, so that the reaction product is fully dispersed in the water; After the stirring is completed, the centrifugal sedimentation mode is immediately switched to, the centrifugal speed is controlled at 400-450r / min, and the centrifugal time is set to 15-20min; Step 3: Screen the precipitates produced after stirring in batches, with 60 ml as one measurement, and screen the precipitates of the same proportion to extract nanocellulose; It is further explained that after the centrifugation, the precipitated material is transferred to an automatic screening device, which sets multiple layers of sieves with different apertures according to the particle size distribution characteristics of nanocellulose, arranged in order from large to small, with the aperture of the top sieve being 0.5 μm, and decreasing in sequence to the aperture of the bottom sieve being 0.05 μm; During the screening process, the precipitate intercepted by each layer of the sieve is collected and measured separately, with 60 ml as a measuring unit. The nanocellulose that meets the particle size requirements is combined and collected as a toughening material in the subsequent preparation process. The centrifugal speed inside the external centrifugal device is controlled at 350 r / min, the heating temperature is controlled at 50° C., and the proportion of water added is 5 times that of concentrated sulfuric acid liquid.

[0060] The sintering aid includes at least one of calcium oxide, magnesium oxide, silicon dioxide, lanthanum oxide and titanium dioxide.

[0061] The sintering aid is a mixture of titanium dioxide and magnesium oxide, and the mass ratio of titanium dioxide to magnesium oxide in the mixture is 1 to 3:1.

[0062] The sintering aid is prepared according to the following method: titanium dioxide and magnesium oxide are mixed according to a mass ratio, zirconium oxide is used as a ball milling ball, the speed of the ball mill is controlled to be 700-900r / min, the ball milling time is controlled to be 4-8h, and dry ball milling is performed to obtain it.

[0063] The pressing process in step six is ​​performed by using an external pressing device, and the pressing time and pressing weight are effectively controlled. The pressing time is controlled at 2-5 minutes, and the pressing weight is set at 5-10N.

[0064] The drying in step six refers to drying the pressed green body, cutting and segmenting the dried green body, and batch drying multiple groups of green bodies after different segments. When the green body is drying, the drying temperature is set at 50-80°C and the drying time is set at 8-12h.

[0065] The sintering in step six refers to placing the green body after segmented drying in a sintering furnace, controlling the sintering temperature at 1400-1600° C., and controlling the sintering time at 5-7 minutes to prepare a toughened alumina ceramic green body.

[0066] In comparative example 1, ceramic powders (alumina ceramics, quartz, and calcite) were weighed, distilled water was used as a ball milling medium, the materials were mixed in a planetary ball mill for 2 hours, and a mixed powder was obtained after drying. The rest of the preparation process of example 4 was repeated to obtain alumina ceramics.

[0067] After testing, in Comparative Example 1, the ceramic bending strength is 285.51 MPa, and the fracture toughness is 4.35 MPa·m1 / 2. The ceramic bending strength in Example 1 is reduced by 14.37%; and the ceramic fracture toughness is increased by 72.87%.

[0068] In comparative example 2, 70 g of distilled water was weighed, stirred for 10 min, and then the pH value was adjusted to 12 with aqueous ammonia to prepare a premixed solution; the rest of the preparation process of Example 2 was repeated to prepare alumina ceramics.

[0069] After testing, in Comparative Example 2, the ceramic bending strength is 295.99 MPa, and the fracture toughness is 3.91 MPa·m1 / 2. The ceramic bending strength in Example 2 is reduced by 6.71%; and the ceramic fracture toughness is increased by 39.39%.

[0070] Test method: 1. Grain morphology and size: Use scanning electron microscope to take pictures of grain morphology, and then use imageJ software to calculate the limit / average grain size and porosity of the pictures; 2. Bending strength: The substrate samples were cut into rectangular standard parts with l = 40 mm and b = 24 mm by laser, and the thickness h of each sample was measured by a screw micrometer. The test samples were placed on an electronic universal testing machine with a span of L = 30 mm, a roller diameter of d = 3 mm, and a loading rate of v = 0.5 mm / min. The critical bending force F of the substrate samples was measured, and the sample strength data was obtained by the strength calculation formula δ = 3FL / 22bh; 3. Fracture toughness: Use WDW electronic universal testing machine to measure the fracture toughness of the material by single edge notched beam method (SENB method), and set the loading rate to 0.05mm / min. The calculation formula is: KIC = Y3PLa / 2bw, and the fracture toughness of the material can be calculated; Where P is the load when the specimen breaks, N; L is the span between supports, mm; a is the depth of the specimen cut, mm; b is the width of the specimen section, mm; w is the height of the specimen section, mm; 4. Thermal conductivity: According to the specific scheme in the national standard GB / T5598-2015, the sample was cut into discs with a diameter of d = 10 mm. The sample and the standard sample of the same thickness were tested by a laser flash thermal diffusion coefficient tester to obtain the thermal diffusion coefficient α and specific heat Cp of the sample. The volume density of the sample was tested by the Archimedean method, and the thermal conductivity of the sample was obtained by the thermal conductivity formula λ = α·Cp·ρ.

[0071] Obviously, the described embodiments are only some embodiments of the present invention, not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field and related fields without creative work should fall within the scope of protection of the present invention. The structures, devices and operating methods not specifically described and explained in the present invention are implemented according to the conventional means in the field unless otherwise specified and limited.

Claims

1. A toughened alumina ceramic, characterized in that: The invention comprises the following components in parts by weight: 2-6 parts by weight of clay, 15-35 parts by weight of nano-aluminum powder, 65-95 parts by weight of alumina powder, 6-14 parts by weight of concentrated sulfuric acid, 6-14 parts by weight of microcrystalline cellulose, 2-5 parts by weight of a sintering aid, 2-5 parts by weight of quartz, 2-5 parts by weight of calcite, 12-16 parts by weight of graphene and 5-7 parts by weight of a binder; The method for preparing the aluminum oxide powder comprises the following steps: Step A1: selecting aluminum salt as an aluminum source and performing recrystallization treatment on the aluminum salt to improve the purity; Step A2: weigh the purified aluminum salt and calculate the amount of the required precipitant (ammonia water) according to the chemical reaction stoichiometric ratio; Step A3: Deionized water is used as the solvent, and the conductivity of the water is controlled to be below 1 μS / cm; Step A4: Select sodium dodecylbenzene sulfonate, accurately weigh the amount, and prepare a solution with a concentration of 0.01-0.05 mol / L with deionized water for later use; Step A5: under stirring conditions, slowly drop the aluminum salt solution into the precipitant solution, monitor the pH, and after the dropwise addition is completed, continue to stir the reaction for 1-2 hours to allow the reaction to proceed fully to obtain aluminum hydroxide precipitate; Then, an aging treatment is performed, and the reaction system is allowed to stand for aging for 6-12 hours, and the aging temperature is controlled at 30-40° C. to obtain an aluminum hydroxide precursor; Step A6: washing the aluminum hydroxide precursor by multiple centrifugal washings, and after washing, using a vacuum filtration device for solid-liquid separation, using a microporous filter membrane with a pore size of 0.1-0.2 μm to obtain a pure aluminum hydroxide precursor; Step A7: The washed aluminum hydroxide precursor is transferred to a high-pressure reactor, deionized water is added according to a solid-liquid ratio of 1:10-1:20 g / mL, and the previously prepared organic additive solution is added, the reactor is sealed, and then placed in a heating furnace for hydrothermal reaction; Step A8: After the hydrothermal reaction is completed, the reactor is allowed to cool naturally to room temperature. After cooling, centrifugal separation is performed again to separate the plate-like crystalline alumina powder. The separated plate-like alumina powder is dried in a vacuum drying oven. The dried product is ground using an agate mortar to obtain the final plate-like crystalline alumina powder.

2. A method for preparing toughened alumina ceramics, characterized in that: The following steps are included: Step 1: Preparation of toughening material: prepare a reaction kettle, inject concentrated sulfuric acid and microcrystalline cellulose into the reactor to mix, and complete the preparation of nanocellulose; Step 2: Preparation of ceramic powder: Nano-aluminum powder and high-purity alumina powder are used as initial raw materials, mixed evenly, and the mixed slurry is dried and ground to obtain ceramic powder; Step 3: Mix the ceramic powder and the sintering aid, use distilled water as a ball milling medium, and perform ball milling on the mixed materials to obtain an alumina slurry; Step 4: adding nanocellulose to alumina slurry and ball milling to obtain a mixed slurry after uniform dispersion; Step 5: mixing the mixed slurry with clay, quartz, graphene, calcite and a binder to obtain a mixed blank; Step six: granulate, press-form, dry and sinter the mixed blank to obtain toughened alumina ceramics.

3. The method for preparing a toughened alumina ceramic according to claim 2, characterized in that: The method for preparing nanocellulose comprises the following steps: Step 1: Prepare a measuring cup and put 10 parts by weight of microcrystalline cellulose into the reactor, then take out 300-400 ml of 45-65% concentrated sulfuric acid and put it into the reactor, and use an external heating device to heat the entire reactor; Step 2: The heating time is controlled within 30-50 minutes. After the color changes after heating, add an appropriate amount of water directly into the reactor, and use an external centrifugal device for stirring and precipitation; Step 3: Screen the precipitates produced after stirring in batches, with 60 ml as one measurement, and screen the precipitates of the same proportion to extract nanocellulose.

4. The method for preparing a toughened alumina ceramic according to claim 1, characterized in that: The sintering aid includes at least one of calcium oxide, magnesium oxide, silicon dioxide, lanthanum oxide and titanium dioxide.

5. The method for preparing a toughened alumina ceramic according to claim 1, characterized in that: The sintering aid is a mixture of titanium dioxide and magnesium oxide, and the mass ratio of titanium dioxide to magnesium oxide in the mixture is 1 to 3:

1.

6. The method for preparing a toughened alumina ceramic according to claim 5, characterized in that: The sintering aid is prepared according to the following method: titanium dioxide and magnesium oxide are mixed according to a mass ratio, zirconium oxide is used as a ball milling ball, the speed of the ball mill is controlled to be 700-900r / min, the ball milling time is controlled to be 4-8h, and dry ball milling is performed to obtain it.

7. The method for preparing a toughened alumina ceramic according to claim 2, characterized in that: The pressing process in step six is ​​performed by an external pressing device, and the pressing time and pressing weight are effectively controlled. The pressing time is controlled at 2-5 minutes, and the pressing weight is set at 5-10N.

8. The method for preparing a toughened alumina ceramic according to claim 2, characterized in that: The drying in step six refers to drying the pressed green body, cutting and segmenting the dried green body, and batch drying multiple groups of green bodies after different segments. When the green body is dried, the drying temperature is set at 50-80°C and the drying time is set at 8-12h.

9. The method for preparing a toughened alumina ceramic according to claim 2, characterized in that: The sintering in step six refers to placing the green body after segmented drying in a sintering furnace, controlling the sintering temperature at 1400-1600° C., and controlling the sintering time at 5-7 minutes to prepare a toughened alumina ceramic green body.

Citation Information

Patent Citations

  • Preparation method of low-cost zirconium dioxide toughened alumina ceramic granular powder

    CN104193307A

  • Magnesium-borate-whisker-enhanced silicon-carbide-based ceramic circuit board substrate material and preparation method therefor

    CN105384455A

  • Electrostatic spinning nanofiber toughened aluminum oxide ceramic and preparation method thereof

    CN113816729A

  • Preparation method of toughened aluminum oxide ceramic body

    CN113968746A

  • Production process of nano aluminum oxide polishing powder

    CN115893461A

Cited By

  • Cellulose nanocrystal-based ceramic material and preparation method thereof

    CN121135468A